Liver Enzymes Abnormalities among Highly Active Antiretroviral Therapy Experienced and HAART Naïve HIV-1 Infected Patients at Debre Tabor Hospital, North West Ethiopia: A Comparative Cross-Sectional Study - Melashu Balew Shiferaw; Ketema Tafess Tulu; Amtatachew Moges Zegeye; Amarech Asratie Wubante (AIDS Research and Treatment)
Liver disease has emerged as the most common non-AIDS-related cause of death in HIV patients. However, there is limited data regarding this condition including our setting in Ethiopia. Hence, liver enzyme abnormalities among highly active antiretroviral therapy (HAART) experienced and HAART naïve patients were assessed in this study. A total of 164 HAART experienced and 164 HAART naïve patients were studied. Blood specimen was collected to determine alanine aminotransferase (ALT) and aspartate aminotransferase (AST), CD4 count, and viral hepatitis. The prevalence of liver enzyme abnormality was 20.1% and 22.0% among HAART experienced and HAART naïve patients, respectively. The HAART experienced patients had higher mean ALT than HAART naïve patients (P=0.002). Viral hepatitis (AOR = 6.02; 95% CI = 1.87–19.39), opportunistic infections (AOR = 2.91; 95% CI = 1.04–8.19), current CD4 count <200 cells/mm3 (AOR = 2.16; 95% CI = 1.06–4.39), and male sex (AOR = 1.83; 95% CI = 1.001–3.33) were associated with elevated ALT and/or AST. In conclusion, liver enzyme abnormalities were high in both HAART experienced and HAART naïve HIV-1 infected patients. Hence, monitoring and management of liver enzyme abnormalities in HIV-1 infected patients are important in our setting.